Digital video-based study habits as mediators of academic performance in university students - Remaycuna-Vasquez, Alberto; Carrión-Barco, Gilberto; Atoche-Silva, Luz Angelica; Vela-Miranda, Oscar Manuel; Horna-Calderón, Víctor Eduardo; Espinoza-Porras, Fátima Rosalía; Fernández-Otoya, Fiorela Anaí (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
In recent years, various studies have been developed regarding academic performance related to self-esteem, cognitive commitment, motivation, among others. However, there is still a limitation in works that analyze to what extent study habits function as mediating factors of academic performance in students. This work aimed to determine to what extent study habits explain academic performance in university students in northern Peru.